Blockchain Integration in Sustainable Letters of Credit Supply Chain - Majumder, Mohammad Ismail; Habib, Professor Md Mamun (International Journal of Supply Chain Management, 2025)
Letters of Credit (LC) are pivotal in global trade finance, providing secure payment assurance to exporters and importers. However, the traditional LC process is laden with inefficiencies, risks of forgery, and delays, particularly in developing countries like Bangladesh. In response to these challenges, Blockchain Database Integration (BDI) is gaining traction as a secure, transparent, and efficient alternative. This study investigates how BDI influences Sustainable Letters of Credit Supply Chains (SLCSC), mediated by the adoption of Technology-based Letters of Credit Supply Chains (LCSC). Drawing on a sample of 400 respondents from LC-related sectors in Bangladesh, the study employed Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM) to assess the validity and reliability of the proposed reflective measurement model. Two key hypotheses were tested, and the results supported both the direct impact of BDI on LCSC and the mediated relationship between BDI and SLCSC through LCSC. The findings confirm that blockchain, when effectively integrated into LC operations via technological platforms and smart contracts, enables a transformative path toward eco-efficient and transparent supply chain practices. The study contributes both theoretically and practically to the discourse on digital trade finance and sustainable development.